Diversidade e estrutura genética de Astronium concinnum Schott e Senefeldera verticillata (Vell.) Croizat, espécies arbóreas da Floresta Atlântica, ES - Vieira, Alessandra Abreu Rodrigues (2017)
Habitat fragmentation due to anthropic disturbance modifies the landscape of forest environments, among them the Atlantic Forest that today is a set of isolated forest fragments. The current situation of this biome has been causing the local extinction of several populations and others have been suffering invaluable losses of genetic variability. Astronium concinnum Schott (Gonçalo-Alves) and Senefeldera verticillata (Vell.) Croizat (Sucanga) are arboreal species that are suitable for use in parks and gardens projects, as well as pharmacological use. Understanding the patterns of genetic diversity of a species is a determining factor in decision making for preservation, management and recovery of degraded areas. In this sense, foliar samples of A. concinnum and S. verticillata were collected in two conservation units, in the Pacotuba National Forest (FLONA) and in the Private Natural Heritage Reserve (RPPN) Cafundó, located in Cachoeiro de Itapemirim, State of Espírito Santo. The main objective of this study was to evaluate genetic diversity using Inter Simple Sequence Repeats (ISSR) molecular markers and, based on the results, to infer about the most appropriate management of these species preservation, besides selecting more genetically divergent trees for seedling production recovery of degraded areas of the region. Also, a comparison was made between four different protocols, aiming at the isolation of pure genomic DNA of the S. verticillata species. For the A. concinnum species, eight primers provided 121 DNA fragments, with 73.55% polymorphism. The genetic diversity of Nei (H) and diversity index of Shannon (I) were 0.312 and 0.473, respectively. The gene flow (Nm) was 10,629. The analysis of molecular variance (AMOVA) identified that, 92.54% of genetic diversity occur within the population. Three groups were identified through Bayesian analysis. By the unweighted arithmetic means clustering method (UPGMA), the formation of seven groups was observed. Aiming the isolation of pure genomic DNA from S. verticillata four protocols were compared. Protocol 1, Doyle and Doyle (1990) modified by the Instituto Agronômico de Campinas (IAC), provided DNA with a purity of 1.96 and the highest mean DNA concentration (224.22 ng / µL). Protocol 2, Doyle and Doyle (1990) modified by IAC, with changes in the concentrations of Polyvinylpyrrolidone (PVP) and ß-mercaptoethanol, provided purity similar to protocol 1 and a mean concentration of 201.02 ng / µL. With protocol 3, Doyle and Doyle (1990) modified by IAC, with changes in the concentrations of PVP, ß-mercaptoethanol and addition of Bovine Serum Albumin (BSA), values of 65.75 ng / µL and 1.5 concentration and purity of DNA, respectively. Finally, in Protocol 4, Doyle and Doyle (1990) with Proteinase K addition, values of 67.6 ng / µL concentration and purity of 1.66 were obtained. The DNA purity results, in protocols 3 and 4, indicated that there was contamination by proteins during 12 the extraction process. It is suggested that protocol 1 be used to obtain good quality S. verticillata DNA. Twelve ISSR primers were used to analyze the genetic diversity of S. verticillata, resulting in a total of 179 amplification products, with 75.97% of polymorphic bands. The results for H and I were 0.329 and 0.503, respectively. The estimated Nm was 13,542. Greater genetic diversity was observed within the populations (94.98%), through AMOVA results and, among populations, the result was 5.02%. Bayesian cluster analysis provided the formation of three groups. The dendrogram obtained by the UPGMA method provided the formation of six groups. Through this research, it was observed that the greatest genetic diversity occurs within the populations, for both species. The most genetically divergent individuals of A. concinnum and S. verticillata have been identified and can be selected as seed trees for the supply of seeds with genetic variability. Also, it was possible to obtain a protocol that resulted in higher quality S. verticillata DNA samples.